The Correlation of Non-alcoholic Fatty Liver Disease with Visceral Fat Area and Thyroid Nodules in Patients with Type 2 Diabetes Mellitus - ZENG Jialing, MENG Yan, DENG Tingting, LI Jinhua, ZHAO Ping (Zhongguo quanke yixue)
Background The prevalence of non-alcoholic fatty liver disease (NAFLD) significantly increases in patients with type 2 diabetes mellitus (T2DM). However, the correlation of NAFLD with visceral fat area (VFA) and thyroid nodules in T2DM patients has been rarely reported. Objective This study aims to investigate the influencing factors for NAFLD in T2DM patients, and the correlation of NAFLD with VFA, thyroid nodules, and thyroid function in this population. Methods Hospitalized T2DM patients in the Department of Endocrinology, the Fourth Affiliated Hospital of Guangxi Medical University (Liuzhou Worker's Hospital) from January 2018 to April 2023 were retrospectively recruited. They were divided into two groups based on abdominal ultrasound findings: NAFLD group and non-NAFLD group. General data, including VFA, subcutaneous fat area (SFA), insulin function, thyroid function, prevalence of thyroid nodules, blood glucose levels, lipid levels, and liver and kidney function were compared between the two groups. Additionally, patients were divided into visceral obesity group (VFA≥100 cm2) and non-visceral obesity group (VFA < 100 cm2) based on VFA. Age, sex, prevalence of NAFLD and thyroid nodule were compared between the two groups. Spearman correlation analyses were employed to investigate factors associated with NAFLD and VFA, as well as their correlation with thyroid nodules. Influencing factors for the volume of thyroid nodules were explored as well. Furthermore, binary Logistic regression analysis was used to determine risk factors for both NAFLD and thyroid nodules in T2DM patients. Receiver operating characteristic (ROC) curve analysis evaluated the predictive value of BMI, waist-hip circumference, and waist-hip ratio, VFA, homeostatic model assessment for insulin resistance (HOMA-IR) in predicting NAFLD in T2DM patients and their optimal cut-off values. Results A total of 578 T2DM patients were enrolled in this study, including 293 (50.69%) patients in the NAFLD group and 285 in the non-NAFLD group. The age of the NAFLD group was significantly lower than that of non-NAFLD group [ (57.0±12.8) years vs. (59.3±11.6) years, P<0.05]. Compared to those of the non-NAFLD group, patients in the NAFLD group had significantly higher body weight, body mass index (BMI), waist circumference, hip circumference, VFA, SFA, glycated hemoglobin (HbA1c), fasting insulin levels (FINS), fasting C-peptide levels (FCP), HOMA-IR, homeostasis model assessment of β-cell function (HOMA-β), free triiodothyronine levels (FT3), serum uric acid (SUA), total cholesterol (TC), triglyceride (TG) and C-reactive protein (CRP), but significantly lower serum creatinine (SCr) (P<0.05). There were 251 cases in the visceral obesity group and 327 cases in the non-visceral obesity group. The age of the visceral obesity group was significantly lower than that of the non-visceral obesity group [ (55.3±13.4) years vs. (60.3±10.8) years, P<0.05]. The incidence of NAFLD was significantly higher in the visceral obesity group than that of non-visceral obesity group (P<0.05). However, there was no significant difference in the prevalence of thyroid nodules between the visceral obesity group and non-visceral obesity group (64.94% vs. 59.82%, P>0.05). Spearman correlation analysis revealed that the occurrence of NAFLD in T2DM patients was positively correlated with body mass, BMI, waist circumference, hip circumference, waist-to-hip ratio, VFA, SFA, HbA1c, FINS, FCP, HOMA-IR, HOMA-β, total triiodothyronine (TT3), FT3, and CRP (P<0.05), but negatively correlated with age (P<0.05). VFA in T2DM patients was found to be significantly correlated with gender, age, height, body mass, BMI, waist circumference, hip circumference, waist-to-hip ratio, SFA, diastolic blood pressure (DBP), FINS, FCP, HOMA-IR, HOMA-β, TT3, FT3, CRP and NAFLD (P<0.05). The thyroid nodule area showed a negative correlation with height, thyroid stimulating hormone (TSH) and waist-to-hip ratio (P<0.05), while it showed positive correlations with sex, age, TT3, TT4 and thyroglobulin (P<0.05). Univariate unconditional Logistic regression analysis revealed that age, weight, BMI, waist circumference, hip circumference, VFA, SFA, HbA1c, FCP, HOMA-IR, FT3, SCr, SUA, TC and TG were the influencing factors for NAFLD in T2DM patients. Binary Logistic regression results demonstrated that body weight (OR=0.962), VFA (OR=1.025), SFA (OR=1.006), FT3 (OR=1.429) and HOMA-IR (OR=1.140) were the influencing risk factors for NAFLD in T2DM patients. Gender (OR=0.342), age (OR=1.073) and free thyroxine (FT4) (OR=1.140) were influencing factors for thyroid nodules in T2DM patients (P<0.05). ROC curve results showed that the area under the curve (AUC) of BMI, waist circumference, hip circumference, waist-to-hip ratio, VFA and HOMA-IR was 0.704, 0.704, 0.705, 0.629, 0.757, and 0.569, respectively. The optimal cut-off value, sensitivity and specificity of them were listed as follows: BMI (25.37 kg/m2, 67.7%, 36.0%), waist circumference (84.5 cm, 67.3%, 36.4%), hip circumference (96.5 cm, 69.4%, 38.9%), waist-to-hip ratio (0.895, 38.8%, 19.1%), VFA (88.4 cm2 in female and 99.45 cm2 in male, 78.9%, 35.3%), and HOMA-IR (3.08, 64.3%, 49.8%) . Conclusion The prevalence of NAFLD and thyroid nodules in T2DM patients significantly increase, but not correlated. Obese T2DM patients, especially those with visceral obesity, are more likely to suffer from NAFLD, thyroid nodules, hyperlipidemia, hyperuricemia and other metabolic diseases. HOMA-IR is a influencing factor for NAFLD in T2DM patients, but it is not a influencing factor for thyroid nodules. BMI, waist circumference, hip circumference and VFA are predictive factors of NAFLD in T2DM patients, and VFA has the highest diagnostic value and HOMA-IR has the lowest value. VFA predicts NAFLD in T2DM patients with the optimal cut-off value of 88.4 cm2, which is equal in females and 99.45 cm2 in males.